IMPLEMENTASI REFORMASI ADMINISTRASI PADA BAGIAN UMUM DAN PERLENGKAPAN SEKRETARIAT DAERAH KOTA BALIKPAPAN - Izmir Novian Hakim; Nur Fitriyah; Anthonius Margono (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research aims to explore to what extent do basic tasks and functions have been conducted in accordance with the spirit of the administrative reform, concerning that any duties and responsibilities require good results. This research employs qualitative approach to gain description and a deep understanding of the Implementation of Administrative Reform in the General Affairs and Supplies Department with analysis data used is the model developed interactive of Miles and Huberman.